The Intersection of Gender Identity and Violence: Victimization Experienced by Transgender College Students - Griner, Stacey B.; Vamos, Cheryl A.; Thompson, Erika L.; Logan, Rachel; Vázquez-Otero, Coralia; Daley, Ellen M. (Journal of interpersonal violence, 2020)
College students disproportionately experience victimization, stalking, and relationship violence when compared with other groups. Few studies explore victimization by the gender identity of college students, including those who identify as transgender. The purpose of this study is to explore the rates of violence experienced by transgender students compared with male and female college students. This study utilized the National College Health Assessment–II (NCHA-II) and included data from students (n = 82,538) across fall 2011, 2012, and 2013. Bivariate statistics and binary logistic regression were conducted to test the relationships between gender identity and victimization. Transgender students (n = 204) were compared with male (n = 27,322) and female (n = 55,012) students. After adjusting for individual factors, transgender students had higher odds of experiencing all nine types of violence when compared with males and higher odds of experiencing eight types of violence than females. Transgender students experienced the highest odds in crimes involving sexual victimization, including attempted sexual penetration (adjusted odds ratio [aOR]: 9.49, 95% confidence interval [CI] = [6.17, 14.59], d = 1.00), sexual penetration without consent (aOR: 9.06, 95% CI = [5.64, 14.53], d = 0.94), and being in a sexually abusive relationship (aOR: 6.48, 95% CI = [4.01, 10.49], d = 0.48), than did male students. Findings reveal increased odds of victimization among transgender students when compared with male and female students. Results demonstrate the need for more comprehensive violence prevention efforts in college settings.